Analisis Akuntansi dan Perpajakan Atas Proses Penjualan Pada Perusahaan Distributor Air Mineral di Surabaya - Angelia Anita Kusumasari; Lusy Lusy (Jurnal Akuntansi dan Pajak, 2023)
Accounting is the art of recording, summarizing, analyzing and reporting file, relating to financial transaction in a business or company. The type of file used in this study is qualitative with file related to sales in October 2022. This study aims to analyze the taxation process, related to sales, as well as observe the truth between sales according to tax regulations and those that have been recorded by the company. The research results show that the company has recorded sales. The recording of sales transactions, also matches the terms of sale and the selling price agreed with the customer. As for taxation, the company has created sales invoices through the e-faktur application. Tax invoices related to Value-Added Tax (VAT) output are in accordance with exiting sales at the company. In October, there is an redeption because all invoices that have been created will be reviewed again. If there is an incorrect invoice, a replacement invoice will be created. In October 2022, PT. LTS pays output VAT in the amount of Rp. 29,218,115 with underpaid SPT.